Post-event processing following social and nonsocial evaluative feedback: The moderating roles of social anxiety and emotion regulation - Altheimer, Gizem. (2017)
Abstract: Post-event processing (PEP) is a process whereby people brood over social events after they occur. In Study 1 (N = 101), we examined whether giving participants social (vs. nonsocial) performance feedback would predict higher PEP following an evaluative task. While this was not supported, we found a pattern suggesting that, in the week following the event, those who were high in social anxiety engaged in consistent PEP after receiving social, but not nonsocial feedback. In Study 2 (N = 200), we also tested the effect of emotion regulation on PEP in those high in social anxiety. Exploratory analyses indicated that those who received social (vs. nonsocial) feedback engaged in higher PEP on day 1. In addition, those who were prompted to regulate their emotions (vs. control) experienced an earlier reduction in PEP. Taken together, these studies find support for social feedback and emotion regulation as potential predictors of PEP.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Psychology.; Advisor: Heather Urry.; Committee: Nancy Kocovski, and Samuel Sommers.; Keywords: Experimental psychology, and Clinical psychology.